OP0128 INTEGRATED LABORATORY ABNORMALITY PROFILES OF UPADACITINIB WITH UP TO 4.5 YEARS OF EXPOSURE IN PATIENTS WITH RHEUMATOID ARTHRITIS TREATED IN THE SELECT PHASE 3 PROGRAM - Charles-Schoeman, C.; Giles, J.T.; Lane, N.; Choy, E.; Furst, D.; Vencovský, J.; Wilson, A.G.; Burmester, G.R.; Shaw, T.; Song, Y.; Camp, H.; Khan, N.; et al. (Annals of the rheumatic diseases, 2021)
Upadacitinib (UPA) is an oral Janus kinase inhibitor approved for rheumatoid arthritis (RA). The safety and efficacy of UPA has been evaluated across a spectrum of patients (pts) with RA in the phase 3 SELECT clinical program.1,2 To describe long-term laboratory profiles (cutoff date: June 30, 2020) associated with exposure to UPA, adalimumab (ADA), and methotrexate (MTX) in pts with RA treated in the SELECT trials. Data were analyzed from 6 randomized controlled UPA RA trials.1,2 The proportions of pts experiencing potentially clinically significant laboratory changes at a single time point were summarized for the following groups: pooled UPA 15 mg once daily (QD; UPA15; 6 trials), pooled UPA 30 mg QD (UPA30; 4 trials), ADA 40 mg every other week (EOW; 1 trial), and MTX monotherapy (1 trial). Pts received UPA with/without background conventional synthetic disease-modifying antirheumatic drugs. Treatment-emergent adverse events are reported as exposure-adjusted event rates (events/100 pt-years [E/100 PY]). Toxicity was graded per OMERACT criteria, or NCI CTCAE for creatine phosphokinase (CPK) and creatinine. 4413 pts received ≥1 dose of UPA (UPA15, n=3209; UPA30, n=1204). Exposures were comparable between treatment groups (Table). Proportions of pts with Grade (Gr) 3 and 4 decreases in hemoglobin were highest with UPA30 and MTX (Table). Rates of anemia, as reported by the investigator, were comparable between UPA15, ADA, and MTX groups (Figure); the frequency of UPA-treated pts who discontinued due to anemia was low in all arms. Gr 3 and 4 decreases in neutrophils and lymphocytes with UPA were dose-dependent and higher vs ADA or MTX. Discontinuations due to neutropenia and lymphopenia were rare (<0.1%). Transaminase elevations were more frequent with UPA and MTX vs ADA; however, the proportion of pts who discontinued due to increases in alanine (ALT) or aspartate aminotransferase (AST) were comparable between UPA15 and ADA, and numerically higher with UPA30 and MTX. CPK elevations were more frequent with UPA (Figure). Most events were asymptomatic, and the 1 case of rhabdomyolysis in the UPA30 group was unrelated to study drug (attributed to influenza). This long-term analysis of UPA-treated pts with RA showed dose-dependent relationships for several laboratory abnormalities. Incidences of these with UPA15 were typically higher than with ADA but similar to MTX, except for increased CPK elevations. Treatment discontinuations due to laboratory abnormalities were infrequent and similar across all treatment groups. [1]Tanaka Y. Mod Rheumatol 2020;30:779–87; 2. Rubbert-Roth A, et al. N Engl J Med 2020;383:1511–21. AbbVie funded this study; contributed to its design; participated in data collection, analysis, and interpretation of the data; and participated in the writing, review, and approval of the abstract. No honoraria or payments were made for authorship. Medical writing support was provided by Russell Craddock, PhD, of 2 the Nth (Cheshire, UK), and was funded by AbbVie. [Display omitted] Christina Charles-Schoeman Consultant of: AbbVie, Gilead, Pfizer, and Sanofi/Regeneron, Grant/research support from: AbbVie, Bristol-Myers Squibb, and Pfizer, Jon T Giles Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, Gilead, Pfizer, and UCB, Grant/research support from: Pfizer, Nancy Lane Consultant of: Amgen, Mallinckrodt, Pfizer, and Roche, Ernest Choy Speakers bureau: AbbVie, Amgen, Bristol-Myers Squibb, Chugai, Eli Lilly, Galapagos, Gilead, Janssen, Novartis, Pfizer, Regeneron, Roche, Sanofi, and UCB, Consultant of: AbbVie, Amgen, Biocon, Biogen, Chugai, Eli Lilly, Gilead, Janssen, Merck Serono, Novartis, Pfizer, Regeneron, Roche, R-Pharm, and Sanofi, Grant/research support from: Bio-Cancer, Biogen, Novartis, Pfizer, Roche, Sanofi, and UCB, Daniel Furst Speakers bureau: AbbVie, Continuing Medical Education, and Novartis, Consultant of: Actelion, Amgen, Bristol-Myers Squibb, Corbus, Galapagos, Novartis, and Pfizer, Grant/research support from: Actelion, Amgen, Bristol-Myers Squibb, Corbus, Galapagos, GSK, NIH, Novartis, Pfizer, Roche/Genentech, and Sanofi, Jiří Vencovský Speakers bureau: AbbVie, Biogen, MSD, Pfizer, Roche, Sanofi, and UCB, Consultant of: AbbVie, Boehringer Ingelheim, Eli Lilly, Gilead, and Octapharma, Anthony G Wilson: None declared, Gerd Rüdiger Burmester Speakers bureau: AbbVie, Eli Lilly, Gilead, Janssen, MSD, Pfizer, Roche, and UCB, Consultant of: AbbVie, Eli Lilly, Gilead, Janssen, MSD, Pfizer, Roche, and UCB, Tim Shaw Shareholder of: May own stock or options in AbbVie, Employee of: AbbVie, Yanna Song Shareholder of: May own stock or options in AbbVie, Employee of: AbbVie, Heidi Camp Shareholder of: May own stock or options in AbbVie, Employee of: AbbVie, Nasser Khan Shareholder of: May own stock or options in AbbVie, Employee of: AbbVie, Jillian Yee Shareholder of: May own stock or options in AbbVie, Employee of: AbbVie, Samuel Anyanwu Shareholder of: May own stock or options in AbbVie, Employee of: AbbVie, Iain McInnes Consultant of: AbbVie, Celgene, Janssen, Novartis, and UCB, Grant/research support from: Celgene, Janssen, Novartis, Pfizer, Roche, and UCB Table 1Pts with potentially clinically significant laboratory changesVariable, n (%)MTX monotherapy (n=314; 637.4 PY)ADA 40 mg EOW (n=579; 1051.8 PY)UPA 15 mg QD (n=3209; 7023.8 PY)UPA 30 mg QD (n=1204; 3091.6 PY)Mean (SD) exposure, weeks106 (67)95 (70)114 (64)134 (66)Median (range) exposure, weeks144 (1, 221)118 (2, 231)136 (0, 232)160 (0, 231)Hemoglobin, g/LGr 3 (70–<80 or decreased 21–<30)28a (9.0)24b (4.2)254d (7.9)169f (14.2)Gr 4 (<70 or decreased ≥30)16a (5.1)16b (2.8)101d (3.2)78f (6.5)Neutrophils, 109/LGr 3 (0.5–<1.0)3a (1.0)3b (0.5)40d (1.2)37g (3.1)Gr 4 (<0.5)1a (0.3)1b (0.2)10d (0.3)5g (0.4)Lymphocytes, 109/LGr 3 (0.5–<1.0)74a (23.7)53b (9.2)802d (25.1)423g (35.5)Gr 4 (<0.5)5a (1.6)3b (0.5)75d (2.3)47g (3.9)ALT, U/LGr 3 (3.0–8.0 × ULN)26a (8.3)13c (2.3)152e (4.8)71h (5.9)Gr 4 (>8.0 × ULN)5a (1.6)4c (0.7)26e (0.8)10h (0.8)AST, U/LGr 3 (3.0–8.0 × ULN)15a (4.8)9c (1.6)101e (3.2)36h (3.0)Gr 4 (>8.0 × ULN)1a (0.3)5c (0.9)18e (0.6)8h (0.7)CPK, U/LGr 3 (>5.0–10.0 × ULN)2a (0.6)3c (0.5)65e (2.0)36i (3.0)Gr 4 (>10.0 × ULN)0a (0)3c (0.5)27e (0.8)15i (1.3)Creatinine, μmol/LGr 3 (>3.0–6.0 × ULN)0a (0)1c (0.2)3e (<0.1)2j (0.2)Gr 4 (>6.0 × ULN)0a (0)4c (0.7)8e (0.3)1j (<0.1)an=312. bn=576. cn=577. dn=3201. en=3199. fn=1193. gn=1192. hn=1195. in=1196. jn=1197ULN, upper limit of normal